A Critical Review of Vermi-Composting in Urban and Peri-Urban Waste Management Apropos Robust Environment - Dey Sarkar, Jayashree; Sarkar, Amrita Kumar; Prasad Lal, Sudhanand (Journal of Agricultural Extension Management, 2023)
Ever-increasing population growth, urbanization, and changing consumption patterns have led to an explosion in the amount of waste produced, especially in urban and periurban areas. Though urban organic waste contains relevant nutrients and organic matter, only 4% of global urban nitrogen (N) and phosphorus (P) sources are presently recycled. Through the vermicomposting process, using earthworms, organic wastes can be transformed into nutrient-enriched compost named vermicompost. Vermicomposting of urban waste, before land application, may be a sustainable waste management option, as the vermicast obtained at the end of the vermicomposting process is rich in plant nutrients and is free from pathogenic organisms. The vermicompost produced is both high in organic carbon (18.83-36.01%) and a potential fertilizer (1.16-2.58% N, 0.42- 1.12% P, and 0.61-2.05% K). The nutrient profile in vermicompost is higher than traditional compost. It enhances soil fertility chemically, physically, and biologically. Vermicompost should be applied in moderate concentration to get maximum yield as high concentration application may impede growth due to the presence of a high concentration of soluble salt in vermicompost. The utilization of vermicompost produced from urban and peri-urban waste in agriculture will facilitate the growth of countries’ economies by lowering the consumption of inorganic fertilizers and avoiding the land degradation problem